TRAJECTOIRE D’UNE FEMME COMBATTANTE DE L’EX-RÉBELLION IVOIRIENNE - Kouamé Walter Kra (European Scientific Journal, ESJ, 2014)
From the case of an ex-woman fighter of the ivorian rebellion, the paper examines the phenomenon of women's participation in armed conflict in terms of their social trajectory. Through an autobiographical approach that focused on the life story as investigative technique, the paper came to the following conclusion: the very poor living conditions, and the struggle against that poverty during her childhood and adolescence, can develop in a woman attitudes, feelings and inherent capabilities as resources for integrating an armed movement and become a fighter.